Al-Tanāṣ al-Adabī fī Masraḥiyah Muḥammad Ṣallā Allāh ʽAlaih wa Sallam li Taufīq al-Ḥakīm - Nisa, Kholifah Wahidatun (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2021)
One of the Egyptian famous writer is Taufiq Al-Hakim. Of the many drama scripts that he wrote, namely